2017
DOI: 10.1159/000453672
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Linking Interparental Aggression to Child Dental Caries

Abstract: Research has garnered support for a systemic view of factors affecting child dental caries that accounts for the influence of social factors such as the family environment. Our previous work has demonstrated the association between mother-to-father emotional aggression and child caries. The present study builds on these results by evaluating pathways that might explain this relation. Families (n = 135) completed a multimethod assessment of mother-to-father emotional aggression, child caries, and several hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Thus, it is questionable whether dental neglect was a signifier or an outcome of maltreatment. To this end, several papers identified the need for further theoretical and empirical inquiry to better understand the intersection between child maltreatment and poor dental health and to provide a more robust basis for clinical diagnosis (e.g., Bhatia et al, 2014; Lorber et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is questionable whether dental neglect was a signifier or an outcome of maltreatment. To this end, several papers identified the need for further theoretical and empirical inquiry to better understand the intersection between child maltreatment and poor dental health and to provide a more robust basis for clinical diagnosis (e.g., Bhatia et al, 2014; Lorber et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Research supports the systematic review of factors affecting child dental caries, including the influence of social factors such as the family environment (Lorber et al 2017). From the population health literature, Fisher-Owens et al (FisherOwens et al 2007) identified five key determinants of health: genetic and biological factors, the social environment, physical environment, health behaviors, and dental and medical care.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is the standard method used to obtain information on IPV 62 . We also only extracted data on IPV and women though there is evidence suggestive that both males and females may be victims of IPV 63,64 ; and IPV affecting men may be associated with the risk of ECC 26 . Also, this is a crosssectional study.…”
Section: Factorsmentioning
confidence: 99%
“…Lorber et al 25 studied children's exposure to domestic violence and the risk for ECC and found no significant relationship between them though a positive trend was observed. However, in households where women were aggressive towards men, the risk for ECC was higher due to high exposure to cariogenic diets 26 .…”
Section: Introductionmentioning
confidence: 99%